1994
DOI: 10.1002/ijc.2910560524
|View full text |Cite
|
Sign up to set email alerts
|

Production of IL‐10 by melanoma cells: Examination of its role in immunosuppression mediated by melanoma

Abstract: Previous studies have shown that IL-10 may modulate immune responses towards the humoral arm by inhibiting production of cytokines involved in cell-mediated responses. In the present studies, we found that mRNA to IL-10 could be demonstrated in 66% of melanoma cell lines by PCR amplification of reverse-transcribed mRNA and in supernatants of the cell lines by ELISA. Release into the supernatants increased approximately 2-fold each day up to 3 days. The MW of 35S-labelled IL-10 secreted by melanoma cells was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
11

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(117 citation statements)
references
References 23 publications
5
101
0
11
Order By: Relevance
“…DC of cancer patients exhibit dysfunction as a result of tumor cells secreting immunosuppressive cytokines such as transforming growth factor g (TGF-g ) [33], vascular endothelial growth factor (VEGF) [34], and IL-10 [35]. A promising means of eliciting tumor-specific antigen presentation to the immune system is to provide optimal DC to induce a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…DC of cancer patients exhibit dysfunction as a result of tumor cells secreting immunosuppressive cytokines such as transforming growth factor g (TGF-g ) [33], vascular endothelial growth factor (VEGF) [34], and IL-10 [35]. A promising means of eliciting tumor-specific antigen presentation to the immune system is to provide optimal DC to induce a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 -11 IL-10 appears to be important in different types of human malignancy. [12][13][14][15][16][17][18] When the expression of IL-10 was evaluated in both the normal and abnormal cervix, it was shown that the severity of squamous intraepithelial lesions correlated with the increased expression of IL-10. The increased level of this immunomodulatory cytokine is localised to the transformation zone.…”
mentioning
confidence: 99%
“…The analysis of the cytokine spectrum displayed by melanoma cells (Becker et al, 1994;Chen et al 1994;Mattei et al, 1994;Dummer and Boni, 1995;Kruger-Krasagakes et al, 1995) revealed that melanoma cells transcribe and secrete IL-10. IL-10 is a cytokine with a variety of effects, including inhibition of monocyte major histocompatibility complex (MHC) class II-dependent antigen presentation, THI cytokine production and inhibition of T-cell proliferation (Howard and O'Garra, 1992;deWaal Malefyt et al, 1993;Becker et al, 1994).…”
Section: Discussionmentioning
confidence: 99%